Peer effects in risk taking - Amrei M. Lahno; Marta Serra-Garcia (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper examines the effect of peers on individual risk taking. In the absence of informational motives, we investigate why social utility concerns may drive peer effects. We test for two main channels: utility from payoff differences and from conforming to the peer. We show experimentally that social utility generates substantial peer effects in risk taking. These are mainly explained by utility from payoff differences, in line with outcome-based social preferences. Contrary to standard assumptions, we show that estimated social preference parameters change significantly when peers make active choices, compared to when lotteries are randomly assigned to them.
Keywords: C91; C92; D03; D83; G02; 330; peer effects; decision making under risk; social comparison; social preferences; laboratory experiment; Entscheidung bei Risiko; Risikopräferenz; Soziale Gruppe; Test